Acorn woodpeckers alter resource use, group size, and spring productivity across an urban landscape - Olivia R. Knapp; Kendra E. Forster; Alexander J. Rurik; Isabelle Hugoniot; Eric S. Reyes; Peter B. Schramm; Corban A. Muthiah; Aaron Wong; Seth C. Wilmoth; Sophia L. McRae; Caleb Courson; Theodore J. Patterson; et al. (Urban Ecosystems, 2026)
Access to suitable resources shapes the evolution and maintenance of avian cooperative breeding by influencing whether an individual will have a greater chance of survival and reproduction by dispersing or remaining on a natal territory. Cooperatively-breeding species exhibit altered dispersal according to food availability and habitat quality, but the relationship between resource use, group size, and reproduction in human-altered landscapes remains to be studied. We examined how urbanization, key resource availability, and resource use relate to differences in group size and number of offspring in an urban population of facultative cooperatively-breeding acorn woodpeckers. Acorn woodpeckers shifted to increased use of ornamental trees, palms, and anthropogenic structures for granaries in more urbanized areas and where oak trees, a key historic food and granary resource, are in lower abundance and proximity. Pair breeding was more prevalent in urbanized areas and seemed to be primarily associated with use of utility poles for granaries. In general, territories with utility poles as granaries and higher urbanization levels hosted smaller group sizes. In contrast, while the number of fledglings was higher in larger groups, it did not vary with urban resources when controlling for group size. Our findings suggest that land conversion levels and the relative availability of historic and novel resources shape habitat quality, resulting in differing patterns of group living and subsequent productivity across the urban landscape. This indicates that while novel resources may enable wildlife to occupy urban areas, they may also influence the social behavior of facultative cooperative breeders.